قياس أثر التدريب في أداء العاملين ( دراسة ميدانية على مديرية التربية بمحافظة البريمي في سلطنة عمان) - ميَا, علي يونس; شيخ ديب, صلاح; الشامسي, سالم راشد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد نشاط التدريب والتنمية من الأنشطة الأساسية في إدارة الموارد البشرية، وتنفق الدول المتقدمة والمنظمات المختلفة أموالاَ طائلة لتدريب العاملين، وهذا يشير إلى اهتمام تلك الدول بالكوادر البشرية والعملية التدريبية مقارنةَ بالدول النامية. وذلك بهدف تحسين الأداء، وتطوير وسائل العمل سعياَ منها نحو المزيد من الكفاءة والفاعلية، وتحسين الإنتاجية. قد هدفت هذه الدراسة إلى قياس أثر التدريب في أداء العاملين بمديرية التربية بمحافظة البريمي في سلطنة عمان، وذلك للتعرف على مستوى تأثير البرامج التدريبية المناسبة في تحسين أداء العاملين ومدى كفاءتها وتصميمها وتقويمها، وكذلك تبيان العلاقة بين مهارات وقدرات المتدرب، والأداء الفعلي الذي يسعى التدريب إلى تحقيقه، واحتياجات العاملين الفعلية من التدريب والتي تتناسب مع اختصاصات ومهام الوظيفة، والسعي لتحقيق غاية أكبر تتمثل في رفع مستوى الأداء لدى العاملين وزيادة إنتاجيتهم، عن طريق الممارسة الفعلية لما اكتسبوه من مهارات وخبرات ومعلومات خلال العمليات التدريبية. Training activity is considered as a main activity in the management of human resources. All developed countries pay a lot of money to train employees. This indicates the interest of these nations in training operation in comparison with developing countries. This aims at developing execution towards more effectiveness and production perfection. The purpose of this study is to investigate the Measurement of training effectiveness on employees execution in education department in Breimy governorate, for recognizing training programs and its effects on employees execution and its range in qualification and the relation between trainee capacities and real execution that training seeks to achieve, in addition to the employees’ real need of training which suits their functional tasks, and the effort to reach a the ultimate objective which is raising the employee’s execution level and increasing their production, by applying practically the new acquired skills.